Contribution of the Dosage of Nt-ProBNP in the Assessment of Pulmonary Embolism Severity in Black African Community - ZANNOU, DJIMON MARCEL; AGBODANDE, KOUESSI ANTHELME; AZON KOUANOU, ANGÈLE; BAGLO, TATIANA; WANVOEGBE, FINANGNON ARMAND; EYISSE, YASMINE; MOUSSE, LATIF (My University, 2015)
Objective: To determine the role of NT-proBNP in the assessment of the severity of pulmonary embolism. Patients and methods: The study was performed at Atinkanmey, a private hospital of Cotonou. It is a retrospective, analytical and transversal study, over a period of 3 years (1 January 2009 to 31 December 2011). The study included 35 patients ≤75 years followed for pulmonary embolism with whom the NT-proBNP dosage was performed. NT-proBNP was compared to other severity criteria such as low blood pressure, tachycardia, Pulmonary Embolism Severity Index, the right ventricular trombosis and dilatation of the right cavities associated with PAH. Results: NT-proBNP is lower than 1000ng /L in 27 patients (77.1%) and higher than 1000ng/L in 8 patients. The sensitivity of NT-proBNP is low compared to severity criteria studied. It varies from 33% to 50%. The specificity is improved and reached 100% when the NT-proBNP is compared to dilation of the right cavities. The best negative predictive value is obtained with low blood pressure (92.6%). The best positive predictive value (PPV) was found by comparing the NT-proBNP to dilatation of the right cavities. Conclusion: The rise of NT-proBNP is not always associated with the presence of gravity criteria studied. Normality seems more associated with lack of dilation of the right cavities.
Keywords: NT-proBNP; Pulmonary embolism; Gravity